THE UNBEARABLE BURDEN OF INVENTION. - Rybczynski, Witold (Hedgehog Review)
The article focuses on the architecture of historical buildings. It presents views of critic Aaron Betsky on the experimentation on architecture of public buildings. It discusses the significance of imitation by several architects including Filippo Brunelleschi, Andrea Palladio and Jacopo Sansovino in Renaissance.